2007
DOI: 10.4049/jimmunol.179.8.5033
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ CTL Priming by Exact Peptide Epitopes in Incomplete Freund’s Adjuvant Induces a Vanishing CTL Response, whereas Long Peptides Induce Sustained CTL Reactivity

Abstract: Therapeutic vaccination trials, in which patients with cancer were vaccinated with minimal CTL peptide in oil-in-water formulations, have met with limited success. Many of these studies were based on the promising data of mice studies, showing that vaccination with a short synthetic peptide in IFA results in protective CD8+ T cell immunity. By use of the highly immunogenic OVA CTL peptide in IFA as a model peptide-based vaccine, we investigated why minimal CTL peptide vaccines in IFA performed so inadequately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
193
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(200 citation statements)
references
References 50 publications
5
193
1
1
Order By: Relevance
“…This process is indispensable for proper priming and activation of TSA-specific naïve T cells. 33, 34 Second, long peptides can provide several MHC class I alleles with ligands, thus permitting a broader cohort of patients to benefit from a vaccine. Third, long peptides can comprise both MHC class I and II epitopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is indispensable for proper priming and activation of TSA-specific naïve T cells. 33, 34 Second, long peptides can provide several MHC class I alleles with ligands, thus permitting a broader cohort of patients to benefit from a vaccine. Third, long peptides can comprise both MHC class I and II epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…Following this line of thought, cancer vaccination with long synthetic peptides 33 , presents a versatile and easily applicable therapeutic platform. Indeed, peptide vaccination was effective in eliciting tumor-protective immunity in animal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that the use of synthetic long peptides can induce more effective cytotoxic T cell (CTL) responses than minimal MHC Class I restricted peptide-based vaccine. 24 We then evaluated the capacity of the D393-CD20 28-47 long peptide (LP) to prime HLA-A2-restricetd CTL response. To this end, mice were immunized either with the D393-CD20 [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] LP or with the HLA-A2-restricted D393-CD20 derived short peptide D393-CD20 [33][34][35][36][37][38][39][40][41] (SP).…”
Section: Tumor Immunologymentioning
confidence: 99%
“…Tindle et al identified E7 [48][49][50][51][52][53][54] (DRAHYNI) as a Th-cell-stimulating epitope that helped to elicit antibody responses to HPV-16 E7 in a mouse model [97]. Recently, multiple studies have indicated that the use of longer versions of CTL peptide epitopes, covering the Th-cell epitope, ensures the induction of sustained CD8 + T cell reactivity in vivo, when compared with using the minimal CTL peptide epitope (E7 [49][50][51][52][53][54][55][56][57] ) [98,99]. Extension of the CTL peptides to longer variants may offer an excellent alternative when external specific CD4 + helper T cell epitopes are not readily available [99].…”
Section: Epitope Selectionmentioning
confidence: 99%